2017
DOI: 10.1038/srep44024
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting gap structure of FeSe

Abstract: The microscopic mechanism governing the zero-resistance flow of current in some iron-based, high-temperature superconducting materials is not well understood up to now. A central issue concerning the investigation of these materials is their superconducting gap symmetry and structure. Here we present a combined study of low-temperature specific heat and scanning tunnelling microscopy measurements on single crystalline FeSe. The results reveal the existence of at least two superconducting gaps which can be repr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
58
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 63 publications
14
58
2
1
Order By: Relevance
“…2 (a) and (b). A similar anomaly was also seen in earlier report [20], which however exhibits like a shoulder around 2 K there, and the authors attributed this anomaly to a very small second superconducting gap. Since the low temperature anomaly observed here is a clear jumping step, not a knee like, this excludes the possibility that it is a second superconducting gap of the FeSe system, since a multiband fitting using the same T c would give rise to a "knee" or "hump" here, not as a sharp step.…”
Section: B Measurement On Specific Heat and Fitting With Different Gsupporting
confidence: 56%
See 2 more Smart Citations
“…2 (a) and (b). A similar anomaly was also seen in earlier report [20], which however exhibits like a shoulder around 2 K there, and the authors attributed this anomaly to a very small second superconducting gap. Since the low temperature anomaly observed here is a clear jumping step, not a knee like, this excludes the possibility that it is a second superconducting gap of the FeSe system, since a multiband fitting using the same T c would give rise to a "knee" or "hump" here, not as a sharp step.…”
Section: B Measurement On Specific Heat and Fitting With Different Gsupporting
confidence: 56%
“…In that work, a similar anomaly of specific heat appears at around 1.25 K and it strongly depends on the concentration of interstitial Fe. (2) In another earlier study [20], the authors observed a similar specific heat anomaly at around 2-3 K, this is much higher than the critical temperature of Al (T c = 1.17 K). (3) Most importantly, in our low temperature specific heat measurements, we find that this anomaly appears to a magnetic field at least up to 2000 Oe, but the critical field H c of Al is about 99 Oe.…”
Section: Magnetic Field Dependence Of Specific Heat In Low Temperamentioning
confidence: 90%
See 1 more Smart Citation
“…Experimentally, scanning tunneling spectroscopy (STS) [39], London penetration depth and thermal conductivity [34] claimed nodal superconductivity. However, measurements of the lower critical field [40], low-temperature specific heat [41,42], other STM [42] and other thermal conductivity studies [43,44] are consistent with nodeless superconducting gap. A cross-over from nodal in the bulk to nodeless at the twin boundary is found from STS [45].…”
mentioning
confidence: 96%
“…Interestingly, it was also shown by STS measurements that the tunneling spectra display a full gap at the twin boundaries (). However, our most recent combined STS and specific heat studies conducted on single crystals grown by pure chemical vapor transport () strongly support multigap node‐less superconducting gap structure throughout the FeSe material ().…”
Section: Fesementioning
confidence: 83%